If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -1(5 + 2x) = 0 3x + (5 * -1 + 2x * -1) = 0 3x + (-5 + -2x) = 0 Reorder the terms: -5 + 3x + -2x = 0 Combine like terms: 3x + -2x = 1x -5 + 1x = 0 Solving -5 + 1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 1x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + 1x = 0 + 5 1x = 0 + 5 Combine like terms: 0 + 5 = 5 1x = 5 Divide each side by '1'. x = 5 Simplifying x = 5
| x+4x-73=72 | | 10/3x2/5 | | 5x+16=2X | | 6x/3-18 | | 3/10(220) | | 2-3t+6+4t-12=9t | | 3c+8=5c+11 | | 2n+8=17 | | 555,555,555+124,135,352,246= | | 3Q-1+10-4+1-1-2=20 | | (1/3)*3(1/4) | | f(2)=3(2) | | 3.50t+5.50=51 | | -7n+10=4n+10 | | 3.60.+s=3 | | (3/5*x)-(2/3)=1 | | -4(-7x+1)+5(8+2x)=-2 | | -1/2z=-10 | | 18=3s | | f(0)=3(0) | | -4y=32+11x | | 2(ab)3+3a+5b= | | 220=2l+2(2/3L) | | -5x^2-40x+45=0 | | -a+4a-9=8a+6 | | 1/3x31/4 | | k+3-2k-6+5k+4=41 | | 8-24+3x=6x+1 | | 4X+73=X+37 | | -3(x+3)=3x+1 | | f(-1)=3(-1) | | (3/5x)-(2/3)=1 |